Fenomena Tumbler Tuku Di Kai Dalam Perspektif Cyber Pragmatik - Mika Charolin; Intan Valiza; Mesya Fadila Sani Harahap; Muhammad Ridho Afarrel; Afriani Sasmita Br Manurung; Oky Fardian Gafari; Herning Puspitarini (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
The viral phenomenon of "tumbler tuku" at PT Kereta Api Indonesia (KAI) is one example of the dynamics of digital communication in the social media era. This case began with a passenger's complaint posted on social media and then escalated into a communication crisis involving multiple parties. The purpose of this research is to examine this phenomenon from a cyberpragmatic perspective, particularly regarding how context functions to understand the intent of utterances in the digital space. This study uses a descriptive qualitative approach by examining utterances on social media, institutional responses, and media coverage. The results indicate that utterances on social media tend to be emotional and judgmental, which can lead to misunderstandings. The virtual context plays a crucial role in rectifying, affirming, clarifying, and underlying the intent of utterances from a cyberpragmatic perspective. Conflicts in the digital public space increase due to misinterpretation of context.